Exploring the Impact of ICT Resources and Organisational Support on Job Satisfaction: A Work-Life Balance Perspective in Private Banks - Aji Dwi Saputro; Zohaib Hassan Sain (BUSMI : Journal of Business and Management Innovations, 2025)
This study explores how Information and Communication Technology (ICT) resources and Perceived Organisational Support (POS) influence employee job satisfaction, with a focus on the mediating role of Work-Life Balance (WLB). The object of research is the workforce within digitally-enabled private banks in Indonesia, where digitalisation and human resource management practices intersect in shaping employee experience. The study addresses the emerging issue where technological flexibility, while beneficial, contributes to blurred work-life boundaries and emotional fatigue. At the same time, organisational support is not always aligned with employees’ evolving needs. Therefore, the objective is to examine both direct and indirect relationships between ICT, POS, WLB, and job satisfaction. A quantitative approach was applied through a structured survey conducted among 125 employees working in private banks located in Central Java and Yogyakarta. Data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) to test the hypothesised relationships. Findings confirm that both ICT resources and POS significantly affect job satisfaction, with WLB playing a mediating role. POS emerged as a stronger predictor than ICT. The results validate Social Exchange Theory as an explanatory framework and show how organisational support and digital tools jointly influence employee well-being. This study concludes that sustainable job satisfaction in digital banking environments requires a dual focus on technological advancement and empathetic organisational practices. Work-life balance should be treated as a strategic component of human resource policies in the digital era.